The cryo-EM structure and physical basis for anesthetic inhibition of the THIK1 K2P channel - Elena B. Riel; Weiming Bu; Thomas T. Joseph; Leila Khajoueinejad; Roderic G. Eckenhoff; Paul M. Riegelhaupt (Proceedings of the National Academy of Sciences, 2025)
THIK1 tandem pore domain (K2P) potassium channels regulate microglial surveillance of the central nervous system and responsiveness to inflammatory insults. With microglia recognized as critical to the pathogenesis of neurodegenerative diseases, THIK1 channels are putative therapeutic targets to control microglia dysfunction. While THIK channels can principally be distinguished from other K2Ps by their distinctive inhibitory response to volatile anesthetics (VAs), molecular details governing THIK channel gating remain largely unexplored. Here, we report a 3.2 Å cryo-electron microscopy structure of the THIK1 channel in a closed conformation. A central pore gate located directly below the THIK1 selectivity filter is formed by inward-facing TM4 helix tyrosine residues that occlude the ion conduction pathway. VA inhibition of THIK requires closure of this central pore gate. Using a combination of anesthetic photolabeling, electrophysiology, and molecular dynamics simulation, we identify a functionally critical THIK1 VA binding site positioned between the central gate and a structured section of the THIK1 TM2/TM3 loop. Our results demonstrate the molecular architecture of the THIK1 channel and elucidate critical structural features involved in regulation of THIK1 channel gating and anesthetic inhibition.